Author's Reply to Vergin's Note on the Paper “Lot Size Scheduling on a Single Machine for Stochastic Demand” - Goyal, S. K. (Management Science, 1976)
Author's Reply to Vergin's Note on the Paper “Lot Size Scheduling on a Single Machine for Stochastic Demand” (Vergin, Roger C. 1976. Note—A note on “Lot size scheduling on a single machine for stochastic demand” by Goyal. Management Sci. 22 823–824).